Genotype-guided versus standard vitamin K antagonist dosing algorithms in patients initiating anticoagulation - Belley-Cote, Emilie P.; Hanif, Hasib; D’Aragon, Frederick; Eikelboom, John W.; Anderson, Jeffrey L.; Borgman, Mark; Jonas, Daniel E.; Kimmel, Stephen E.; Manolopoulos, Vangelis G.; Baranova, Ekaterina; Maitland-van der Zee, Anke H.; Pirmohamed, Munir; Whitlock, Richard P. (Thrombosis and Haemostasis, 2015)
Variability in vitamin K antagonist (VKA) dosing is partially explained by genetic polymorphisms. We performed a meta-analysis to determine whether genotype-guided VKA dosing algorithms decrease a composite of death, thromboembolic events and major bleeding (pri-mary outcome) and improve time in therapeutic range (TTR). We searched MEDLINE, EMBASE, CENTRAL, trial registries and conference proceedings for randomised trials comparing genotype-guided and standard (non genotype-guided) VKA dosing algorithms in adults initiating anticoagulation. Data were pooled using a random effects model. Of the 12 included studies (3,217 patients), six reported all components of the primary outcome of mortality, thromboembolic events and major bleeding (2,223 patients, 87 events). Our meta-analysis found no significant difference between groups for the primary outcome (relative risk 0.85, 95 % confidence interval [CI] 0.54–1.34; heterogeneity X2=4.46, p=0.35, I2=10 %). Based on 10 studies (2,767 patients), TTR was significantly higher in the genotype-guided group (mean difference (MD) 4.31 %; 95 % CI 0.35, 8.26; heterogeneity X2=43.31, p< 0.001, I2=79 %). Pre-specified exploratory analyses demonstrated that TTR was significantly higher when geno-type-guided dosing was compared with fixed VKA dosing (6 trials, 997 patients: MD 8.41 %; 95 % CI 3.50,13.31; heterogeneity X2=15.18, p=0.01, I2=67 %) but not when compared with clinical algorithm-guided dosing (4 trials, 1,770 patients: MD –0.29 %; 95 % CI –2.48,1.90; heterogeneity X2=1.53, p=0.68, I2=0 %; p for interaction=0.002). In conclusion, genotype-guided compared with standard VKA dosing algorithms were not found to decrease a composite of death, thromboembolism and major bleeding, but did result in improved TTR. An improvement in TTR was observed in comparison with fixed VKA dosing algorithms, but not with clinical algorithms.
Keywords: Anticoagulants; genetics; meta-analysis; pharmacogenomics; warfarin